Productivity of Hand Line Fishing Gear based on Bait Type Operating in West Halmahera Waters - Taeran, Imran; M. Abdullah, Rommy; A. Harahap, Zulhan (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This study aims to: (1) describe the characteristics of the fish caught in each type of hand line that consisting: type, number, weight, hook depth, and size category of fish caught, (2) analyze the productivity of hand line fishing gears. The research method used was a survey method by following fishing operations on the two hand-lines around FADs. The research was conducted from July to August 2019 in the West Halmahera sea, North Maluku. This research used descriptive analysis and productivity analysis. The results of the study showed that the artificial bait bait type hand line caught 4 species of fish with a total of 135 individuals, while the hand line with natural bait caught as many as 30 individuals. The weight of the catch on the artificial bait type hand line was 258 kg while the natural bait type hand line catch was 757 kg. The artificial bait hand line had better catches at a depth of 40 m, while the natural bait type catches more at a 50 m depth. The artificial bait type hand line had a productivity value ranging from 3.7-6.6 kg/trip with an average productivity of 5.15 kg/trip. The natural bait type hand line had a higher value, which ranged from 8.43-21.71 kg/trip with an average productivity of 16.00 kg/trip.